Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing - Lee, Roger (Springer, 2017)
The 9th ACIS International Conference on Software Engineering, Artificial Intelligence, Networking, and Parallel/Distributed Computing, held in Phuket Thailand on August 6 – 8, 2008 is aimed at bringing together researchers and scientist, businessmen and entrepreneurs, teachers and students to discuss the numerous fields of computer science, and to share ideas and information in a meaningful way. This publication captures 20 of the conference’s most promising papers, and we impatiently await the important contributions that we know these authors will bring to the field.